Applications of biotechnology to Brachiaria - Tohme, Joseph M.; Palacios, Natalia; Lenis, S.; Roca, W. (International Center for Tropical Agriculture, 1996)
Advanced biotechniques offer the potential for greater precision and efficiency in genetic manipulation of crop species. Applications of molecular markers in Brachiaria include assessment of genetic variation, gene tagging, and genetic mapping. In particular, recent applications of molecular-marking techniques to apomixis provided strong evidence of single-gene inheritance of reproductive mode in Brachiaria. Regeneration protocols for Brachiaria have been worked out and plants of four Brachiaria species have been regenerated. These tools provide a basis for a project aimed at fine-mapping the apomixis gene, and its possible cloning and transfer to other crop species.